2016
DOI: 10.1039/c5cy01372k
|View full text |Cite
|
Sign up to set email alerts
|

Development of silica-supported frustrated Lewis pairs: highly active transition metal-free catalysts for the Z-selective reduction of alkynes

Abstract: A supported Lewis acid/base systems based on a triphenyl phosphine fragment and Piers' reagent (HB(C6F5)2) or BArF have been prepared and characterized. Both materials show unprecedented catalytic activity in Z-selective hydrogenation of 3hexyne to Z-3-hexene with a selectivity up to 87%. Other alkynes can also be hydrogenated Z-selectively, albeit with moderate yields. The activity of the supported phosphine/HB(C6F5)2 adduct is similar to the only homogeneous example reported thus far based on bridged B/N fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…[3] An otable exception is the semihydrogenation of alkynes catalyzed by an intramolecular FLP that was reported by Repo et al [4] In that case, mechanistic investigationss howed that the protolysis of the FLP under the reaction conditions yields an amine-hydroborane that initiates the catalytic cycle by hydroboration of the alkyne. [5] Ap rotodeborylation of the alkenylborane yields then, in ah ighly stereoselective reaction, the cis-alkene. [6] We recently reported reversible H 2 activation by the boroxypyridine 3.…”
Section: Introductionmentioning
confidence: 99%
“…[3] An otable exception is the semihydrogenation of alkynes catalyzed by an intramolecular FLP that was reported by Repo et al [4] In that case, mechanistic investigationss howed that the protolysis of the FLP under the reaction conditions yields an amine-hydroborane that initiates the catalytic cycle by hydroboration of the alkyne. [5] Ap rotodeborylation of the alkenylborane yields then, in ah ighly stereoselective reaction, the cis-alkene. [6] We recently reported reversible H 2 activation by the boroxypyridine 3.…”
Section: Introductionmentioning
confidence: 99%
“…A similar reaction has also been realized via a hydridoborane/silica-supported phosphine FLP. 83 Additionally, Wang and coworkers also have reported that the simple, highly Lewis acidic hydroborane HB(C6F5)2 can hydrogenate simple alkenes via a related hydroboration -hydrogenolysis mechanism, 84 which will be discussed in more detail in section 4.1. Overall, the wealth of FLP reactivity with H2 has uncovered two main hydrogenation mechanisms.…”
Section: Dihydrogenmentioning
confidence: 99%
“…This FLP was characterized by DRIFT spectroscopy as well as MAS NMR spectroscopy. It shows a remarkable activity and selectivity in the hydrogenation of alkynes . In contrast, Xing et al.…”
Section: Introductionmentioning
confidence: 95%
“…Supported FLPs for heterogeneously catalyzed hydrogenation reactions are mentioned by Szeto et al. as well as Xing et al . Szeto et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation